Ortorettifica di foto e aree storiche per lo studio delle dinamiche ambientali in regioni montane - Pulighe, Giuseppe (GEOmedia, 2009)
Airborne historical images orthorectification for mountain regions environmental dynamics studies Often the recovery of historical data from aerial photographs involves problems (poor quality of the frames and total lack of metadata about the frame camera). The problem can be better handled by adopting modern techniques of digital photogrammetry, using procedures and methods of ortho-projection with the support derived from analysis of the current territory and DTM (Digital Terrain Model) accuracy and finally with the production of mosaic. This work concerns the ortho-rectification process of 16 historic aerial photos for a test area of South Tyrol, Italy, on the Gruppo Aeronautico Italiano planimetric fly (Volo GAI) performed between 1954 and 1956. The aim is to bring out this photogrammetric historical heritage and provide a contribution to the knowledge of South Tyrol landscape and its evolution over the half century, with tools of consultation and multi-temporal comparison.